Simulation and Control of Inverted Pendulum System Dynamics over Control Area Network using TrueTime - Abdulrab, H.Q.A. (Institute of Electrical and Electronics Engineers Inc., 2020)
Inverted pendulum is one the most popular systems that has been used and studied in the field of control engineering. Even its simplest form is an under-actuated system and highly unstable with high non-linear dynamics. Therefore, it is a challenging control task and have been referred to as benchmark for testing control algorithms. This paper discusses modelling and control of inverted pendulum using Linear Quadratic Regulator (LQR) controller. Then, the same model and controller are inserted to a real time Simulink model for the purpose of analysing the scheduling of tasks and testing control area network (CAN) performance. This is done by utilizing True Time toolbox. In this paper both nonlinear and linearized models were analysed. Four sensors, an actuator and a controller are used in analysing the response of the inverted pendulum. Different scheduling techniques and the response of the system after changing the period of one of the sensors in the system were also investigated. By changing the period of one sensor and maintaining the other 3 sensors, the system became unstable as discussed throughout the paper. Â© 2020 IEEE.